Membentuk Karakter Anak : (Analisis Peran Orang Tua, Sosial dan Agama) - Yusril Ihsa Nur Rizqi; Nahdia Ilma Nafisa; Lulu’ Qonita (LPTNU Sumenep, 2024)
This article addresses everyday life issues that need collective attention. Community life cannot be separated from the presence of social and religious values. Both of these values play a significant role in maintaining harmony within society. These values are also essential in shaping the character of children, ensuring their lives are more organized and positive. Character formation through parental education within the family plays a crucial role in instilling social and religious values. Social values instilled in children are derived from prevailing customs and traditions. Social values are established to create a better community life. Meanwhile, religious values are drawn from teachings rich in moral values. Instilling religious values in children can foster positive character traits, as these teachings are based on morals relevant to contemporary life. Nurturing children's character through social and religious values makes them positive individuals who are responsive to issues arising in society.